Education and Economic Harmonious Development: A Path to Sustainable Development - Yixuan Wang; Lijun Wang (Environment and Social Psychology, 2025)
Education is one of the key avenues for investing in human capital and is also an important means of enhancing society’s research and development capabilities and technological levels. Therefore, investment in education has become an overlooked factor, affecting the quality of economic growth. Since the reform and opening-up, with the continuous improvement of China’s economic development level, the role of education has become increasingly prominent, and investment in education by central and local governments at all levels has continued to increase. Especially since achieving the goal in 2012 of having fiscal education expenditure exceed 4% of GDP, education funding has entered the "4% era," effectively ensuring the level of educational development. However, while educational development can positively drive economic growth, the relationship between the two is not simply linear. The impact of education on the quality of economic growth depends on multiple conditions, among which the matching of the education investment structure is one of the key factors determining the influence of education on the quality of economic growth[1]. Comprehensive Financial Report. This article will delve into the structure of educational investment and its interaction with the quality of economic growth, aiming to provide recommendations for the effective policy arrangement of educational investment and industrial structure to improve the quality of economic growth.